Pengaruh E-Service Quality Dan E-Trust Terhadap Repurchase Intention (Studi Pada Pengguna Lazada Mahasiswa FISIP Undip) - kurniasari, nadya aghnia; Widayanto, Widayanto (Universitas Diponegoro, 2021)
Abstract: The business sector and the use of information technology are indispensable because it is to support the needs of society in the modern era which emphasizes speed, practicality, convenience, security and comfort in business activities. The purpose of the research is